Optimization of Cyber Law as A Legal Basis for Handling Cyber Crime in Indonesia - Marliyanti, Marliyanti (YHMM PUBLISHING, 2023)
Utilization of information and communication technology has changed the behavior of society and human civilization globally. The development of information and communication technology has led to rapid social, economic and cultural changes. In line with the development of internet technology which makes conveniences in the order of life but besides that it also causes the emergence of crimes that utilize the internet which are called cybercrimes or crimes through the internet network. Cyber Law becomes the legal basis in the law enforcement process against crimes by electronic and computer means, in other words, cyber law is needed to tackle cybercrime. By optimizing cyber law as a legal basis in cybercrime cases, it is expected that information and communication technology crimes can reduce the crime rate